A Narrative Inquiry of an English as a Foreign Language (EFL) Teacher’s Experiences in Working with Special Needs Students - Jumainah Jumainah (General English Education, 2023)
This study is intended to unravel how an EFL teacher working in a special needs school teaches her students. The central issues of this study are challenges and strategies employed by the teacher, government concern, readiness, and future expectations of the teacher. Narrative inquiry is carried out as the method of the study. This study involves a participant who has been teaching as an EFL teacher for special needs students for more than seven years. The in-depth narrative interview is conducted to collect the data. To ensure the trustworthiness of the results, the researcher confirms the interpretation of the data with the participant. From the story told by the participant, it is concluded that the biggest challenge faced by the teacher in teaching special needs students is growing their motivation. Thus, the teacher shall be wise in planning the lessons based on each students’ characteristics to enhance their learning motivation. Furthermore, in relation to the government, supports in forms of training and material availability have been given by the Indonesian government. In terms of readiness, most of the English teachers working with special needs students have limited knowledge and experiences at the initial stage of their careers. However, the teachers learn along the way through trials and errors and from a series of training provided to develop their professional skills. In the future, it is expected that the English pre-service teachers can be prepared to teach special needs students as a part of their training and education. Furthermore, the existing teachers are expected to continue learning from different media so that they can keep improving the quality of their teaching.